Embedding Concepts of Sustainable Development in Environmental Education - J. Usha, Rani; Swati, Kumari; Aditi, Singh; B. Siva, Prasad (INTI International University, 2025)
Humans evolved in the realm of nature. During evolution, anthropogenic activities led to an imbalance of natural ecosystems thereby causing environmental disasters. An increase in population, rapid industrialization, urban development, and changes in food consumption patterns are major drivers of environmental degradation. Though these are inevitable as a part of development, the nexus of environmental degradation and economic growth are directly linked with the conservation of various environmental compartments including soil, water, air, and biodiversity. Hence, sustainable development is considered the ultimate goal of the interrelationship of Man and the environment. In this context, environmental education is the need of the hour in educating society about the rational use of natural resources and the importance of Sustainable Development. To build a responsible society, the idea of including environmental education in the broader scope of education for development is imperative. Therefore, to assess the importance of environmental education for sustainable development, a perspective on Sustainable Development Goals (SDGs) from college students is attempted. The major objective of the paper was to assess the sensitization and dissemination of skills, attitudes, and behavior of the students with respect to Sustainable Development of Goals in Environmental Education. Methods of environmental education for sustainable development were imparted to the experimental and control group of students. Results indicated a significant difference between the groups in terms of environmental education, perception, and skills of the students from both groups. Further, students who imparted the knowledge on SDGs in Environmental Education showed more sensitization and perception with respect to SDGs, especially on water, biodiversity, climate change, poverty & hunger when compared to the students who were exposed to the conventional teaching methods of environmental education. Outcomes of the study contribute to the development of new methods of environmental education for sustainable development among college students.